MEK1/2 inhibition by binimetinib is effective as a single agent and potentiates the actions of Venetoclax and ABT‐737 under conditions that mimic the chronic lymphocytic leukaemia (CLL) tumour microenvironment. (16th May 2018) - Crassini, Kyle; Shen, Yandong; Stevenson, William S.; Christopherson, Richard; Ward, Chris; Mulligan, Stephen P.; Best, O. Giles
Summary: The survival and proliferation of chronic lymphocytic leukaemia (CLL) cells is driven by multiple signalling pathways, including those mediated by the B cell, Toll‐like and chemokine receptors. Many of these pathways converge on the same signalling molecules, including those involved in the Raf‐1/MEK/Erk1/2‐MAPK pathway. We investigated the effects of the MEK1/2 (also termed MAP2K1/2) inhibitor, binimetinib, against CLL cells cultured under conditions that mimic aspects of the tumour microenvironment. Binimetinib blocked CLL cell survival induced by stroma‐conditioned media and phorbol myristylate (PMA). Binimetinib was also significantly more toxic towards CLL cells cultured in the presence of either anti‐IgM antibody or stroma‐derived factor‐1α (SDF‐1α) and reduced CLL cell cycle progression and proliferation. Furthermore, binimetinib significantly increased the sensitivity of CLL cells co‐cultured with CD40 ligand (CD40L)‐expressing fibroblasts to the BH3‐mimetics ABT‐737 and Venetoclax (ABT‐199) via a mechanism involving down‐regulation of Mcl‐1 (MCL1) activity and Bim (BCL2L11) and Bcl‐xL (BCL2L1) expression. Collectively, these data suggest that binimetinib may have both cytotoxic and cytostatic effects on CLL cells by blocking microenvironment‐derived signals known to drive survival and proliferation. The combination of binimetinib with a BH3 mimetic may be an effective treatment strategy for CLL, particularly against the proliferative fraction of the disease within the tumour microenvironment.